PERAN MBTI KEPRIBADIAN TIPE JUDGING (J) DAN PERCEIVING (P) DALAM MANAJEMEN WAKTU PENGERJAAN SKRIPSI MAHASISWA BIMBINGAN DAN KONSELING TINGKAT AKHIR ANGAKATAN 2022 UNIVERSITAS SLAMET RIYADI TAHUN 2026 - Brevine Luckia Breezi; Hera Heru Sri Suryanti; Eko Adi Putro (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Brevine Luckia Breezi THE ROLE OF MBTI PERSONALITY TYPES JUDGING (J) AND PERCEIVING (P) IN TIME MANAGEMENT FOR THESIS COMPLETION AMONG FINAL-YEAR GUIDANCE AND COUNSELING STUDENTS CLASS OF 2022 AT SLAMET RIYADI UNIVERSITY IN 2026 The purpose of this study was to determine the role of MBTI Personality Types Judging (J) and Perceiving (P) in Time Management for Thesis Completion among Final Year Guidance and Counseling Students Class of 2022 at Slamet Riyadi University in 2026. This research was conducted at Slamet Riyadi University. The subjects of this study were Guidance and Counseling students from the class of 2022/2023 who were in the process of completing their thesis. The research instruments used were observation guidelines, interviews, and documentation. Data collection techniques were carried out through observation, interviews, and documentation. The data obtained were then analyzed through several stages, including summarizing, concluding, and verifying. Based on the results of data analysis, it was found that students with the Judging (J) and Perceiving (P) MBTI types have different ways of managing time during the thesis completion period. The Judging (J) type strictly follows schedules and is structured, whereas the Perceiving (P) type relies more on mood and is flexible.